Cortisol awakening response and additive serotonergic genetic risk interactively predict depression in two samples: The 2019 Donald F. Klein Early Career Investigator Award Paper. Issue 6 (24th April 2019) - Vrshek‐Schallhorn, Suzanne; Stroud, Catherine B.; Doane, Leah D.; Mineka, Susan; Zinbarg, Richard E.; Redei, Eva E.; Craske, Michelle G.; Adam, Emma K.
Abstract: Background: The serotonin system and hypothalamic pituitary‐adrenal (HPA)‐axis are each implicated in the pathway to depression; human and animal research support these systems' cross‐talk. Our work implicates a 5‐variant additive serotoninergic multilocus genetic profile score (MGPS) and separately the cortisol awakening response (CAR) in the prospective prediction of depression; other work has shown that the serotonin transporter polymorphism 5HTTLPR predicts CAR and interacts with the CAR to predict depression. Methods: We tested the hypothesis that a 6‐variant MGPS (original plus 5HTTLPR) would interact with CAR to predict prospective depressive episode onsets in 201 emerging adults using four annual follow‐up interviews. We also tested whether MGPS predicted CAR. We attempted replication of significant findings in a sample of 77 early adolescents predicting depression symptoms. Results: In sample 1, MGPS did not significantly predict CAR. MGPS interacted with CAR to predict depressive episodes; CAR slopes for depression steepened as MGPS increased, for risk or protection. No single variant accounted for results, though CAR's interactions with 5HTTLPR and the original MGPS were both significant. In sample 2, the 6‐variant MGPS significantly interacted with CAR to predict depression symptoms. Conclusions: Higher serotonergic MGPS appears to sensitize individuals to CAR level—for better and worse—in predicting depression. Abstract : ADAA 2019 Donald Klein Award Manuscript